VD_FINDINFO HC / 2012 / 777 vom 23. November 2012 - VD Tribunal cantonal (2012)
PROLONGATION DU BAIL À LOYER, ANNULABILITÉ, RÉSILIATION | 271 al. 1 CO, 271 CO, 271a al. 1 let. a CO, 271a al. 2 CO, 272 al. 1 CO, 272 al. 2 CO, 272b al. 1 CO